2022
DOI: 10.2147/nss.s339567
|View full text |Cite
|
Sign up to set email alerts
|

Non-Constructive Ruminations, Insomnia and Nightmares: Trio of Vulnerabilities to Suicide Risk

Abstract: Objective Nightmare distress, nightmare frequency and anxiety are related to suicidal risk. Ruminations are a factor maximizing the risk of suicide. Research has identified two types of ruminations: constructive ruminations and non-constructive ruminations. As per our knowledge, no study has verified the links between non-constructive ruminations and sleep disorders and their role in the development of suicidal risk. We aimed to highlight the impact of non-constructive ruminations on nightmares, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
1
3
0
1
Order By: Relevance
“…These correlation analyses were conducted for good sleepers and poor sleepers respectively. The results showed homogeneity between the two groups andare consistent with the existing scientific literature [ 8 , 13 ]. In addition, constructive ruminations were negatively associated with dysfunctional beliefs about sleep and anxiety.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These correlation analyses were conducted for good sleepers and poor sleepers respectively. The results showed homogeneity between the two groups andare consistent with the existing scientific literature [ 8 , 13 ]. In addition, constructive ruminations were negatively associated with dysfunctional beliefs about sleep and anxiety.…”
Section: Discussionsupporting
confidence: 91%
“…Few studies differentiate between types of rumination and their distinct links in relation to sleep disorders. Faccini et al [ 13 ] have shown that only non-constructive ruminations are associated with nightmare distress, insomnia and increased psychopathological risk including suicidal risk in the general population. Tighe et al [ 14 ] have highlighted in their work that it is important to distinguish between different types of repetitive thinking.…”
Section: Introductionmentioning
confidence: 99%
“…Further, sleep symptoms can cause great distress and may increase the risk of suicidal ideation. 6 Thus, there is a need for more successful management of sleep disturbance in subjects suffering from anxiety and depression. data and drafted the manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…People with insomnia usually experience greater levels of depression and anxiety. Further, sleep symptoms can cause great distress and may increase the risk of suicidal ideation 6 . Thus, there is a need for more successful management of sleep disturbance in subjects suffering from anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Oft begegnen sie diesem Wunsch bereits frühzeitig durch dysfunktionales Verhalten, wie Schlafperioden tagsüber oder besonders frühe Bettzeiten, wodurch es aber nur zu einer Verstärkung des „insomnischen Teufelskreises“ mit vermehrtem Wachliegen, Grübeln, steigender Anspannung und Suizidalität kommt. Gleichzeitig berichten Patienten mit nächtlichem „nicht-konstruktivem Grübeln“ gehäuft über kombinierte insomnische Symptome und Suizidalität, oft auch im Zusammenhang mit Albträumen [ 18 ].…”
Section: Prävention Und Behandlungunclassified